Gambaran Penggunaan Pillbox Pasien Hipertensi dalam Rangka Meningkatkan Kepatuhan Minum Obat di Kecamatan Lubuk Kilangan - Najmiatul Fitria; Lailaturrahmi Lailaturrahmi; Yelly Oktavia Sari (Warta Pengabdian Andalas, 2022)
Hypertension is a chronic disease with long-term treatment. According to World Health Organization (WHO) data, only 36.8% of hypertensive patients take hypertension medication properly. Adherence is the most common problem in the treatment of hypertension. This adherence can be improved by providing counseling regarding the use of medicine boxes as a tool that can increase patient compliance in taking medicine. This community service activity aims to improve medication adherence in hypertension patients in Lubuk Kilangan District, Padang City. The counseling session was held among 35 participants. Based on sociodemographic data, it was found that there were differences in the number of female and male participants (80%: 20%), as well as the level of education and type of work (unemployment 94%) . Therefore, community service is expected to improve medication adherence in hypertensive patients (>80%). If medication adherence has increased, it is hoped that the incidence of hypertension can be reduced.